IMPROVING ACCOUNTING AND REPORTING OF FINANCIAL ASSETS IN BUDGET ORGANIZATIONS IN THE CONNECTION OF INNOVATIVE AND DIGITAL ECONOMY - Shaymatova Nargiza Ashurovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article scientifically examines the basics of financial asset accounting and preparation of financial reporting in budget organizations. Methodological problems related to the accounting of financial assets and financial reporting data are presented. Scientific proposals and practical recommendations for improving the accounting and reporting of financial assets have been developed.